Emotional Intelligence, Attachment Style, and Marital Satisfaction among Married Employees - Vasquez-Salcedo, Ma. Zandra Bonnine; Natividad, Maria Jocelyn (Journal of Interdisciplinary Perspectives, 2025)
This study explores emotional intelligence and attachment style as determinants of marital satisfaction among married employees at a polytechnic state college in the Bicol Region, specifically in Camarines Sur. A mixed-method research design was utilized to collect both qualitative and quantitative data from the respondents. Using purposive and convenience sampling techniques, 114 married employees were involved. The main data for this study was collected through three standardized questionnaires, with five participants who scored high on the Kansas Marital Satisfaction Scale selected for in-depth interviews. The study revealed that most respondents were females, aged 40-59, married for 1-10 years, regular faculty employees, and belonged to the middle class with a monthly income between Php 43,829 and Php 76,699. The majority of respondents have average emotional intelligence and score high on secure attachment style while being average in anxious and avoidant subscales, with high levels of marital satisfaction. The themes for the study's variables were life skills, relationship perspective, and shared values. Lastly, there is no significant relationship between emotional intelligence and attachment style, implying that these are not good predictors of marital satisfaction for the respondents considered. Given the absence of correlation between emotional intelligence and attachment style in predicting marital satisfaction, therapists and counselors should consider integrating alternative therapeutic interventions that aim to enhance emotional intelligence, foster closer and more secure bonds, and cultivate strong and fulfilling marital relationships. It is also essential to explore the role of contextual variables that could moderate or mediate the relationship between emotional intelligence, attachment styles, and marital satisfaction, such as socioeconomic factors, cultural backgrounds, or specific life circumstances.